Authorities and Options for Funding USSOCOM Operations - Loredo, Elvira N. (RAND Corporation, 2014)
This report examines mechanisms, sources, and inter-Service agreements for funding special operations forces (SOF) operations and provides recommendations to reduce the frequency and duration of disputes between the United States Special Operations Command, the Military Departments, and Geographic Combatant Commands over their respective funding responsibilities for SOF.